High‐throughput fabrication of carbonized electrospun polyacrylonitrile/poly(acrylic acid) nanofibers with additives for enhanced electrochemical sensing. Issue 43 (26th April 2020) - Tan, Huey Ling; Sanira Putri, Maria Kana; Idris, Siti Shawalliah; Hartikainen, Niklas; Abu Bakar, Noor Fitrah; Keirouz, Antonios; Radacsi, Norbert
Abstract: Lightweight, polyacrylonitrile‐derived electrodes with different additives were fabricated using high‐throughput nozzle‐free electrospinning. The electrospun precursor nanofibers (PNFs) containing iron oxide, gold nanoparticles, or reduced graphene oxide (rGO) were subjected to oxidative stabilization and carbonization to obtain a carbon‐rich conductive nanofiber structure. Scanning electron microscopy showed that the carbon nanofibers contracted between 11 and 55% while the Fourier‐transform infrared spectroscopy confirmed that the carbon nanofibers were thermally stable. Thermogravimetric and differential scanning calorimetry results revealed that the cross‐linking of the chain molecules and cyclization were completed. Next, cyclic voltammetry results indicated that the electroactivity of the modified screen‐printed carbon electrodes was decreased by 85% due to the presence of carbon glue. The modified device presented significant enhanced electrochemical responses with the inclusions of nanoparticles, with rGO showing a 2.13 times higher electroactive surface area, followed by iron oxide (two times) and gold nanoparticles (1.37 times) than the equivalent PNFs. Abstract :